An Extensive Survey of Image Integrity Approaches and Its Perspectives - Bhagat, Amit; Dubey, Rajshree (International Journal of Computer Sciences and Engineering, 2015)
The Storage of digital information is increasing day by day and at the same time new multimedia broadcasting services has also been developed. This development motivated research on copyright-protection and authentication schemes to be applied to these services. One Possible solution is to apply labelling which is a low level system that works upon the bit-stream. Another one is a high level, graphically inlaid, non-deletable system i.e. watermarking. This paper focuses on authentication and watermarking and presents methods that are proposed for the particular cases of still images. The effects of these methods to JPEG and other image formats are to be analyzed, as well as its sensitivity to image manipulations, are expounded and evaluated.